2012
DOI: 10.1371/journal.pone.0045356
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of Subphenotype Association with Systemic Lupus Erythematosus Susceptibility Loci: A European Cases Only Study

Abstract: IntroductionSystemic Lupus Erythematosus (SLE) shows a spectrum of clinical manifestations that complicate its diagnosis, treatment and research. This variability is likely related with environmental exposures and genetic factors among which known SLE susceptibility loci are prime candidates. The first published analyses seem to indicate that this is the case for some of them, but results are still inconclusive and we aimed to further explore this question.MethodsEuropean SLE patients, 1444, recruited at 17 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
1
22
2
Order By: Relevance
“…A study on individuals of European descent showed an association between lupus and variants within the MECP2 gene [11]. Another study regarding gene association in SLE concluded that the susceptibility of genes including MECP2 was correlated with SLE in individuals of European ancestry [10]. A study of the Korean population confirmed that there were significant associations between the variants of SNPs within MECP2 in Korean patients and systemic lupus erythematous [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study on individuals of European descent showed an association between lupus and variants within the MECP2 gene [11]. Another study regarding gene association in SLE concluded that the susceptibility of genes including MECP2 was correlated with SLE in individuals of European ancestry [10]. A study of the Korean population confirmed that there were significant associations between the variants of SNPs within MECP2 in Korean patients and systemic lupus erythematous [5].…”
Section: Introductionmentioning
confidence: 97%
“…Also, MECP2 has an ability to recruit DNA methyltransferase1 (DNMT1), which causes inactivation of gene expression. Single nucleotide polymorphisms (SNPs) of the MECP2 gene have been associated with SLE pathogenesis in some studies [9,10]. A study on individuals of European descent showed an association between lupus and variants within the MECP2 gene [11].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the XKR4 gene seem to be associated with the effect of the dopamine iloperidone antagonist (used in schizophrenia treatment) [151]; this finding may provide important information with respect to patient response to this drug. Meanwhile, a polymorphism in XKR6 was correlated with lupus nephritis which is a defect in patients with SLE [152] which is characterized by the immune system attacking the cells and tissues of the host, thereby leading to inflammation in various organs of the body. However, the role of XKR6 in the development of this disease yet remains unclear.…”
Section: Phospholipid Scramblases In Human Diseasesmentioning
confidence: 99%
“…Recently, however, several genotype-phenotype association studies on systemic lupus erythematosus and generalized vitiligo have been conducted, which identified specific phenotype-associated gene variants [9,10,11]. Therefore, a better understanding of the relationships between genotypes and phenotypes of the disease may help to further elucidate disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%